Implementation Of Activity-Based Learning Model To Increase Aqidah Akhlak Learning Motivation of Students in The IVth Class Madrasah Ibtidaiyah NW AIK AMPAT - Zohrah, Hera Primayanti; Umarella, Samad (IAIN Ambon, 2023)
Student learning motivation is an important factor in educational success. This research aims to increase students' learning motivation in the Aqidah Akhlak subject through the application of an activity-based learning model. The research method used is Classroom Action Research (PTK) with two cycles. Each cycle involves the stages of planning, action, observation, and reflection. The research results show that the activity-based learning model is able to increase students' learning motivation. In the first cycle, student learning completion only reached 42.11%, but increased to 89.47% in the second cycle. These results indicate that an activity-based approach can be an effective strategy in increasing student motivation and learning outcomes.